Integrated Marketing Communication on Visiting Decisions at the Festival Teluk Jailolo, West Halmahera North Maluku - Simabur, Lisda Ariani; Triandika, Lulus Sugeng; Bailussy, Wahyuni; Zainuddin (Jurnal Manajemen Bisnis, 2023)
The promotion mix activities carried out by the West Halmahera Regency Tourism Office were carried out to attract attention so that tourists would come to visit the Festival Teluk Jailolo, West Halmahera Regency. This study was conducted to know and analyze the influence of integrated marketing communications proxied with variables advertising, public relations, personal selling, direct marketing, and interactive marketing on the decision to visit the Festival Teluk Jailolo, West Halmahera Regency. This research is a type of survey research by taking a sample of tourists who visit the Festival Teluk Jailolo held annually by the local government of West Halmahera Regency. The samples in this study were tourists who were or had visited the Festival Teluk Jailolo which was taken by a simple random sampling method with a total of 96 respondents. Data collection techniques using questionnaires and analysis methods used using multiple linear regression analysis with the help of the smart PLS program. The results showed that the variables of advertising, personal selling, and direct marketing had a positive and significant effect on the decision to visit the Festival Teluk Jailolo while the variables of public relations and interactive marketing did not affect the decision to visit the Festival Teluk Jailolo.